2020
DOI: 10.1002/lary.28912
|View full text |Cite
|
Sign up to set email alerts
|

Minor Parotidectomy Complications: A Systematic Review

Abstract: Objectives To report descriptive statistics for minor parotidectomy complications. Methods A systematic review was performed, selecting 235 studies for analysis. The incidence of complications was tabulated, and descriptive statistics calculated. Outlier studies, 1 standard deviation above the mean, were reexamined to determine potential causal factors for each complication. All studies were examined for statistically significant differences for any potential causal factor. Results The pooled incidence of mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 208 publications
(490 reference statements)
3
22
0
5
Order By: Relevance
“…Nonetheless, tumor recurrence, facial nerve paralysis, and other complications (Frey's syndrome [FS], sialocele, and salivary fistula) continue to be reported following all the above‐mentioned surgical interventions 5,19–20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, tumor recurrence, facial nerve paralysis, and other complications (Frey's syndrome [FS], sialocele, and salivary fistula) continue to be reported following all the above‐mentioned surgical interventions 5,19–20 …”
Section: Introductionmentioning
confidence: 99%
“…17,18 Nonetheless, tumor recurrence, facial nerve paralysis, and other complications (Frey's syndrome [FS], sialocele, and salivary fistula) continue to be reported following all the above-mentioned surgical interventions. 5,[19][20] To date, all published meta-analyses provide a headto-head comparison for only two interventions 10,15,21,22 ; however, there is a lack of evidence regarding which type of parotid surgery is associated with the least facial nerve paralysis (temporary or permanent), recurrence, FS, sialocele, and salivary fistula. Therefore, a comprehensive comparative study of different parotid surgical interventions for benign tumors would be of a great value to guide surgeons and help for presurgical counseling of patients who are scheduled for parotid surgery.…”
mentioning
confidence: 99%
“…However, an obvious scar on the face and neck after using the MBI is unavoidable, even with meticulous closure. According to previous studies regarding parotid surgeries, long-term evaluation by questionnaires seems to indicate high scar dissatisfaction 22 , 23 . Some authors have even reported that scars represent the most important long-term issue 22 .…”
Section: Discussionmentioning
confidence: 83%
“…Both rates are well below the reported incidence of 2.9%. 24,25 A similar amount of patients in the outpatient vs inpatient cohorts experienced a postoperative seroma (2.21% vs 0.5%, P = .16) and a postoperative infection (2.21% vs 3.02%, P = .65) (Table 2). Additionally, the readmission rate was 1.47% in the outpatient group and 2.01% in the inpatient group (P = .71), both lower than the national reported rate of 3.9%.…”
Section: Discussionmentioning
confidence: 89%